Electronic materials - Kwok, H. L. (PWS, 1997)
This book is divided into six parts: The basic structures of solids; Electrical properties of solids; p-n junctions and related devices; Optical properties of solids; Magnetic and superconducting properties of solids; and Micromachines, sensors, and packaging materials.